La Pire Aventure d’Yvain: Aventure, conjointure, manufacture dans Le Chevalier au Lion / The Worst Adventure of Yvain: Adventure, Conjointure , Manufacture in Le Chevalier au Lion - Jacques-Kees Noble-Kooijman (Anastasis: Research in Medieval Culture and Art, 2019)
In his Novel « Yvain » adapted from an original Celtic Tale Chrétien de Troyes named « Pesme Aventure » the mythical Episode which constrains Yvain to stand a last qualifying Proof. In this Episode Chrétien has inserted the Description of a weaving Factory where three hundred captives Maiden (« pucelles ») are working in awful Conditions. This Passage has been considered for Decades as an Evidence for a social and economic Reality of the XIIth Century presenting an unwonted Evocation of a supposed unfair exploitation of these Working girls. In a courtly Novel where feudal Realism is enhanced with the Myth of Folktales it was at least surprising. and should be justified. These young Ladies, Subjects of a King from « The Isle of Maiden », are Captives who Yvain rescues out of her Prison in triumphing over two diabolical Champions. Beside the Theme of a mythical Custom the Working girls' Lament remains difficult to understand in his economic Details. The shameful Situation the Girls are living should be reconsidered and it is necessary to re-examine the Structure of the Novel in order to understand the Signification and Integration of the Episode in it. A new Interpretation of the Words chosen by the Author for the Girls' Complaint could be fit to rejuvenate the Controversy upon its Signification.